Fast Pyrolysis of Lignin and Its Derived Products at Low Temperatures - Chua, Yee Wen (Curtin University, 2019)
This thesis investigates the structural changes of chars produced during fast pyrolysis of lignin and its derived compounds at low temperatures, providing new insights into the lignin pyrolysis mechanism. The low-molecular-weight portion of lignin plays a key role in char structural changes during lignin pyrolysis at low temperatures. The thesis also provides direct evidences on the interactions between the low- and high-molecular-weight portions of lignin, which lead to the formation of more condensed char structures.